2018
DOI: 10.2134/agronj2016.11.0666
|View full text |Cite
|
Sign up to set email alerts
|

Phenology and Biomass Production of Adapted and Non‐Adapted Tropical Corn Populations in Central Iowa

Abstract: Biofuel production in the midwestern United States has largely focused on corn (Zea mays L.) grain for ethanol production and more recently, corn stover for lignocellulosic ethanol. Tropical corn refers to corn adapted from tropical regions. Growing tropical germplasm in temperate environments is not attractive for grain yield, but shows promise for biomass production through taller and more vigorous plants with thick stems and long leaves. The comparison between tropical corn populations and their temperate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
1
3
0
1
Order By: Relevance
“…These studies have found morphometric variables are better able to predict biomass outcomes during both vegetative and early reproductive growth. Overall, this study and previous ones suggest that plant height could be an indicator of non-grain and total biomass production [7].…”
Section: Plant Height and Diametersupporting
confidence: 76%
See 1 more Smart Citation
“…These studies have found morphometric variables are better able to predict biomass outcomes during both vegetative and early reproductive growth. Overall, this study and previous ones suggest that plant height could be an indicator of non-grain and total biomass production [7].…”
Section: Plant Height and Diametersupporting
confidence: 76%
“…In addition, multiple non-adapted tropical germplasm have been grown in temperate conditions. Prior studies have shown tropical maize has significant vegetative growth and plant height when grown under temperate conditions [7]. This is favorable when exploring the potential of a germplasm to produce high amounts of non-grain biomass.…”
Section: Introductionmentioning
confidence: 99%
“…In this environment, the SM(o) reached 0.47, while in Gama the HI fell to 0.37. The results reported by Infante et al (2018) show that the HI in maize is equivalent to 0.36 and when the plants adapt to the environment, the HI oscillates between 0.30 and 0.41.…”
Section: Productive Efficiency Of Cropsmentioning
confidence: 97%
“…In Gama, the higher yields were found in HB(o) and IB(o), with 22.55 and 20.90 pods per plant at 159 DAS, respectively (Figure 2A). According to Infante et al (2018), when cultivars adapt to the environment, they increase grain production and decrease biomass production. In this case, beans have adapted better to Simijaca than to Gama.…”
Section: Maize and Bean Yieldmentioning
confidence: 99%
“…Comparado con el germoplasma templado, los genotipos tropicales suelen ser más altos, tienen mayor área foliar, tallos más gruesos y mayor producción de biomasa aparejado de una mayor estructura de sostén y una menor partición a grano (Giaveno y Ferrero, 2003;Muttoni et al, 2013;Infante et al, 2018). El contenido de FDA fue mayor en M2 que en M1 (Figura 12), esto coincide con varios autores (Lewis et al, 2004;Darby y Lauer, 2002;Hansey et al, 2010) quienes asocian su incremento a los procesos de senectud que sufre la planta durante el llenado de granos.…”
unclassified